2007
DOI: 10.1016/j.amjcard.2007.03.081
|View full text |Cite
|
Sign up to set email alerts
|

Atrial and Ventricular Rate Response and Patterns of Heart Rate Acceleration during Maternal–Fetal Terbutaline Treatment of Fetal Complete Heart Block

Abstract: Terbutaline is used to treat fetal bradycardia in the setting of complete heart block (CHB); however, little is known of its effects on atrial and ventricular beat rates or patterns of heart rate (HR) acceleration. Fetal atrial and ventricular beat rates were compared before and after transplacental terbutaline treatment (10 to 30 mg/day) by fetal echocardiography in 17 fetuses with CHB caused by immune-mediated damage to a normal conduction system (isoimmune, n = 8) or a congenitally malformed conduction syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 12 publications
1
31
0
1
Order By: Relevance
“…351,352 fMCG has led to modifications in medical therapy of arrhythmias in some cases. [329][330][331]353 Unlike fetal electrocardiography, fMCG allows raw signal analysis even in the presence of an irregular rhythm. fMCG holds an inherent advantage over fetal electrocardiography in signalto-noise ratios because the conductance properties of magnetic signals are not affected by poor conductivity of fetal and maternal tissues.…”
Section: Fetal Magnetocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…351,352 fMCG has led to modifications in medical therapy of arrhythmias in some cases. [329][330][331]353 Unlike fetal electrocardiography, fMCG allows raw signal analysis even in the presence of an irregular rhythm. fMCG holds an inherent advantage over fetal electrocardiography in signalto-noise ratios because the conductance properties of magnetic signals are not affected by poor conductivity of fetal and maternal tissues.…”
Section: Fetal Magnetocardiographymentioning
confidence: 99%
“…Regardless of the origin (immune mediated or structural CHB), the use of β-sympathomimetics (terbutaline, salbutamol, isoprenaline) to augment fetal ventricular rates when <55 bpm has been reported. 353 β-Sympathomimetics are reasonable to use in fetuses with heart rates <55 bpm or in fetuses with higher heart rates if there is underlying severe CHD or symptoms of fetal heart failure or hydrops. Terbutaline appears to be well tolerated, although maternal resting heart rates of 100 to 120 bpm and benign ectopy are commonly encountered.…”
Section: Av Blockmentioning
confidence: 99%
“…13- 19 Jaeggi et al reported a significant improvement in the outcome of fetal CAVB simultaneously with the introduction of routine perinatal treatment guidelines in 1997. 9 Hutter et al obtained an improved survival rate of >90% by initiation of maternal high-dose dexamethasone at the time of CAVB detection and maintenance of this dose during pregnancy, with addition of β-sympathomimetics to keep the fetal heart rate above 55 beats/min.…”
Section: Benefits and Risks Of Transplacental Treatmentmentioning
confidence: 99%
“…2,7-9,11, 12 There is limited evidence for the clinical efficacy of transplacental treatment of congenital AVB. [13][14][15][16][17][18][19] Steroids and i.v. immunoglobulins are given as anti-inflammatory treatment, while β-sympathomimetics are used for fetal pacing.…”
mentioning
confidence: 99%
“…Maternal betamimetic therapy for fetuses with ventricular rates Ͻ55 bpm has also been given, with minimal benefit in most reports. 6,[12][13][14] …”
mentioning
confidence: 99%